Early warning technique research of surface subsidence for safe mining in underground goaf in Karst Plateau zone - Zhe, Yalei; Hou, Kepeng; Niu, Xiangdong; Liang, Wei (Frontiers in Earth Science, 2023)
Underground mining in Karst Plateau landform area may cause the loss of support for the upper rock stratum, resulting in rock collapse and large-scale subsidence of the ground surface. Also, the formation of a large-scale goafs may further lead to geo-hazards such as collapse, water gushing, slope instability and so on in the area. To reduce the impact of goaf settlement on local strata stability, this paper established a standardized safe mining detection model for goafs based on the geological safety characteristics of mining goafs. With reference to the statistical analysis of the geological conditions in the mining area, a numerical model with 358 goafs and the proposed mining area was established using FLAC 3D numerical software. The surface subsidence and variations of plastic zone in the mining area were comprehensively analyzed. The results indicated that there was a correlation between the stability of the mining area and the geological occurrence conditions of the goafs. By quantitatively taking the values from standardized safety mining detection models, the standardized safety mining detection and warning technique was finally established. The findings can provide technical guidance for safety detection and early warning in the whole process of underground goaf mining in Karst Plateau karst development zone.